Induction of apoptosis and anti HSV-1 activity of 3-(phenethylamino)demethyl(oxy)aaptamine from a Malaysian Aaptos aaptos - Zalilawati, Mat Rashid; Yosie, Andriani; Khozirah, Shaari (2015)
The present study was investigated the cytotoxic activity of a new aaptaminoid of A. aaptos against human myeloid leukemia cell line HL-60 and murine myelomonocytic leukemia cell line WEHI-3B, as well as the mode of cells death and antiviral activity against Herpes simplex virus type 1 HSV-1, infected normal mammalian cells, Cercopithecus aethiops African green monkey kidney cell line VERO. Cell viability was evaluated by Methyl Thiazole Tetrazolium (MTT) assay, following the induction of apoptosis assessment by light microscopy and fluorescence microscopy (Acridine orange/ Propidium iodide (AO/PI) double staining analysis) while using hydrogen peroxide (H2O2) as a standard. The anti-HSV-1 activity was evaluated using neutral red uptake assay. A new alkaloid 3-(phenethylamino)demethyl(oxy)aaptamine(8-methoxy-2-(phenethylamino)-9H-benzo[d,e][1,6] naphthyridin-9-one) (1) and aaptamine (8,9-dimethoxy-1H-benzo[d,e][1,6]-naphthyridin) (2) strongly reduced HL60 viability while also showing cytotoxicity against WEHI-3B, in which the mode of both cells death was through induction of apoptosis. In anti-herpetic investigation against HSV-1, only compound 2 showed strong anti-HSV-1 activity. The compounds however did not exert significant cytotoxic effect on VERO, confirming their tumour-selective cytotoxicity. Result concluded that compounds 1 and 2 produced a good cytotoxicity activity on HL-60 and WEHI-3B. Both compounds inhibited the cells via apoptotic cell death mechanism. In addition, compound 2 also exhibited a good antivirus activity on HSV-1.